A Cohort Pilot Study on HIV-Associated Neuropsychological Impairments in Hemophilia Patients - Riva, Silvia; Cutica, Ilaria; Krampe, Caspar; Reinecke, Laura F.; Russell-Edu, William; Santoro, Cristina; Rocino, Angiola; Santagostino, Elena; Rusconi, Vega; Pravettoni, Gabriella (Frontiers in Human Neuroscience, 2015)
Despite advances in the management of HIV infection with the introduction of combination antiretroviral therapy, it is well known that HIV can directly infect the central nervous system and, as a result of such infection, neuropsychological impairments can be manifested. In this study, we tried to determine whether seropositivity was associated with a poor neuropsychological performance in patients with hemophilia and HIV. Such a cohort of patients is very often underrepresented and understudied in the HIV literature. To amend such a gap, we carried out an extensive neuropsychological evaluation on these patients, and compared their performance with that of a group of seronegative hemophilia patients. The results revealed that HIV infection in HIV-seropositive (HIV+) hemophilia patients was associated with deficits in attention, short-term memory, abstraction, and visual recognition. Such results are still preliminary and explorative due to the small cohort of patients enrolled. However, the results do seem to have some important implications for day-to-day functioning, as the level of impairment detected may cause difficulties in completing common everyday tasks such as maintaining adherence to complex medication regimens or maintaining social life activities. Continued research into the mechanisms related to HIV and neurocognitive dysfunction may provide targets for interventions that could have meaningful consequences in the real world for HIV hemophilia patients.